Mycobacterium tuberculosis phosphoenolpyruvate carboxykinase is regulated by redox mechanisms and interaction with thioredoxin - Machová, Iva; Snašel, Jan; Zimmermann, Michael; Laubitz, Daniel; Plocinski, Przemyslaw; Oehlmann, Wulf; Singh, Mahavir; Dostál, Jiři; Sauer, Uwe; Pichová, Iva (The Journal of biological chemistry, 2014)
Tuberculosis remains a major health concern worldwide. Eradication of its causative agent, the bacterial pathogen Mycobacterium tuberculosis, is particularly challenging due to a vast reservoir of latent carriers of the disease. Despite the misleading terminology of a so-called dormant state associated with latent infections, the bacteria have to maintain basic metabolic activities. Hypoxic conditions have been widely used as an in vitro system to study this dormancy. Such studies identified a rearrangement of central carbon metabolism to exploit fermentative processes caused by the lack of oxygen. Phosphoenolpyruvate carboxykinase (Pck; EC 4.1.1.32) is the enzyme at the center of these metabolic rearrangements. Although Pck is associated with gluconeogenesis under standard growth conditions, the enzyme can catalyze the reverse reaction, supporting anaplerosis of the tricarboxylic acid cycle, under conditions leading to slowed or stopped bacterial replication. To study the mechanisms that regulate the switch between two Pck functions, we systematically investigated factors influencing the gluconeogenic and anaplerotic reaction kinetics. We demonstrate that a reducing environment, as found under hypoxia-triggered non-replicating conditions, accelerates the reaction in the anaplerotic direction. Furthermore, we identified proteins that interact with Pck. The interaction between Pck and the reduced form of mycobacterial thioredoxin, gene expression of which is increased under hypoxic conditions, also increased the Pck anaplerotic activity. We thus propose that a reducing environment and the protein-protein interaction with thioredoxin in particular enable the Pck anaplerotic function under fermentative growth conditions.
Keywords: Mycobacterium Tuberculosis; Thioredoxins; Citric Acid Cycle; Bacterial Proteins; citrátový cyklus; Gene Expression Regulation, Enzymologic; Hypoxia; thioredoxiny; regulace genové exprese u bakterií; oxidace-redukce; Enzyme Kinetics; Phosphoenolpyruvate Carboxykinase; regulace genové exprese enzymů; bakteriální proteiny; fosfoenolpyruvátkarboxykinasa (závislá na ATP); Metabolism; Oxidation-Reduction; Phosphoenolpyruvate Carboxykinase (ATP); Thioredoxin; Gene Expression Regulation, Bacterial; Mycobacterium tuberculosis